Targeted Therapy for Medullary Thyroid Cancer: A Review - Priya, S. R.; Dravid, Chandra Shekhar; Digumarti, Raghunadharao; Dandekar, Mitali (Frontiers in Oncology, 2017)
Medullary thyroid cancers constitute between 2 and 5 percent of all thyroid cancers. The 10-year overall survival rate of patients with localised disease is around 95% while that of patients with regional stage disease is about 75%. Only 20% of patients with distant metastases at diagnosis survive 10 years which is significantly lower than for differentiated thyroid cancers. Cases with regional metastases at presentation have high recurrence rates. Adjuvant external radiation confers local control but not improved overall survival. The management of residual, recurrent or metastatic disease till a few years ago was re-surgery with local measures such as radiation. Chemotherapy was used with marginal benefit. The development of targeted therapy has brought in a major advantage in management of such patients. Two drugs – vandetanib and cabozantinib have been approved for use in progressive or metastatic MTC. In addition, several drugs acting on other steps of the molecular pathway are being investigated with promising results. Targeted radionuclide therapy also provides an effective treatment option with good quality of life. This review covers the rationale of targeted therapy for medullary thyroid cancer, present treatment options, drugs and methods under investigation, as well as an outline of the adverse effects and their management.